1996
DOI: 10.1128/aem.62.11.3997-4002.1996
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis of antibiotic resistance patterns in fecal streptococci, a method to differentiate human and animal sources of fecal pollution in natural waters

Abstract: Discriminant analysis of patterns of antibiotic resistance in fecal streptococci was used to differentiate between human and animal sources of fecal pollution in natural waters. A total of 1,435 isolates from 17 samples of cattle, poultry, human, and wild-animal wastes were obtained, and their ability to grow in the presence of four concentrations of five antibiotics (chlortetracycline, halofuginone, oxytetracycline, salinomycin, and streptomycin) was measured. When the resulting antibiotic resistance patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 21 publications
6
98
1
2
Order By: Relevance
“…Using only a subset of the available antibiotics in the analysis resulted in lower correct classification rates, which is similar to results obtained by Harwood et al (2000). However, in other studies, higher correct classification rates were obtained using a subset of antibiotics (Wiggins 1996;Hagedorn et al 1999).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using only a subset of the available antibiotics in the analysis resulted in lower correct classification rates, which is similar to results obtained by Harwood et al (2000). However, in other studies, higher correct classification rates were obtained using a subset of antibiotics (Wiggins 1996;Hagedorn et al 1999).…”
Section: Discussionsupporting
confidence: 81%
“…Multiple antibiotic resistance (MAR) typing, using of single or multiple concentrations of antibiotic, is a method that has been used to differentiate sources of E. coli and faecal streptococci by testing bacterial resistance to antibiotics commonly associated with human and animal treatment, as well as with animal feed (Cooke 1976;Kaspar et al 1990;Wiggins 1996;Parveen et al 1997;Parveen and Tamplin 1998;Hagedorn et al 1999;Wiggins et al 1999Wiggins et al , 2003Harwood et al 2000;Kelsey et al 2003). Similar to other reports (Cooke 1976;Kaspar et al 1990), we previously found that E. coli isolated from human source were more resistant to antibiotics than nonhuman source isolates (Parveen et al 1997).…”
Section: Introductionsupporting
confidence: 55%
“…The single resistance pattern (pattern A; Table 2) dominating sample 4 contains six of the eight antibiotics tested. The high incidence of a single resistance pattern in the point source of contamination is in agreement with the observation made by Wiggins (1996) of homogeneous populations in chicken and turkey bacterial isolates. Incidentally, sampling point 3 was more heterogeneous than any of the other sampling points, probably due to the heterogeneous sources of bacteria, e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The faecal coliforms isolated from the poultry-processing plant ef¯uent (sampling point 4) showed high MAR indices which is similar to the observations of Krumperman (1983) who reported that MAR indices for E. coli from wild animals were generally low, but much higher for humans and poultry. Cluster analysis based on the various resistance pro®les identi®ed at the different sampling points supports the suggestion of Krumperman (1983), Wiggins (1996) and Parveen et al (1997) that characteristic MAR pro®les may be used to differentiate sources of AR bacterial contamination. In this study, one large cluster was present in the ef¯uent of the chicken meat-processing plant (sampling Table 3) con®rming this as a point source of AR bacterial contamination.…”
Section: Discussionsupporting
confidence: 63%
“…Microbiological methods include: ratios of faecal coliforms to faecal streptococci (Geldreich and Kenner 1969); the presence of Rhodococcus coprophilus (Mara and Oragui 1981); the presence of some phenotypes of Bifidobacterium species (Mara and Oragui 1983); the presence of some phenotypes of Bacteroides species (Kreader 1995); ribotypes of Escherichia coli (Carson et al 2001;Parveen et al 1999); repetitive DNA sequences of E. coli (Dombek et al 2000); antibiotic resistance patterns (Wiggins 1996;Harwood et al 2000); serogrouping of F-specific RNA (F-RNA) bacteriophages (Furuse et al 1978); bacteriophages specific for various strains of Bacteroides fragilis (Tartera et al 1989;Puig et al 1999) and phage typing of Staphylococcus aureus (Zierdt et al 1980). The ideal would be to have a single test to determine the origin of faecal pollution.…”
Section: Introductionmentioning
confidence: 99%